Fotocatalisadores magnéticos ZnO-Ag/CoFe2O4 aplicados na degradação de ibuprofeno - Campos, Mylena Ferreira (2021)
In the present work, the performance of Ag/ZnO/CoFe2O4 magnetic photocatalysts in the photocatalytic degradation of Ibuprofen (IBP) was evaluated. This study considered the use of pure Ag/ZnO (5% Ag) and also use the Ag/ZnO/CoFe2O4 magnetic catalysts containing different amounts (5, 10 and 15% wt) of cobalt ferrite (CoFe2O4). The catalysts were characterized by X-ray diffraction (XRD), photoacoustic Spectroscopy, Scanning Electron Microscopy (SEM) and Zero Charge Point (PCZ). The reaction parameters studied were: IBP concentration, catalyst concentration, adsorption and photolysis, influence of the matrix, radiation source (solar and artificial) and the effect of organic additive. At the end of the photocatalytic tests, the best conditions were defined. The results indicated the feasibility of magnetic separation of the synthesized catalysts. The photocatalytic activity was directly affected by the ferrite load. The higher the nominal load of ferrite, the lower the performance in ibuprofen degrading. It was also observed that the smallest amount of ferrite studied was enough for the catalyst to be recovered and reused. The adsorption and photolysis tests did not show significant results in the IBP degradation. In addition, it was possible to verify that the aqueous matrix, the use of solar radiation and the addition of additive (acid formic) interfered direct in the process. The catalyst reuse tests indicated that it can be recovered and reused at least three times without considerable catalytic activity loss.